An Overview of the Result of Drugs on the Workforce of Surakarta in 2023 - Kusumaningsih, Diah; Susilowati, Indah Tri; Adi, Omry Tri Asmara (Indonesian Journal of Global Health Research, 2023)
The number of drug abuse has increased every year, if this continues, it is feared that Indonesia will lose a generation of the nation. The government has drawn up a National Action Plan for the Prevention and Eradication of Drug Abuse and Trafficking (RAN P4GN) which aims to tackle drug abuse in institutions, one of which is by examining drugs on workers and prospective workers as a condition for hiring employees. This study aims to provide an overview of drug use among workers in Surakarta City in 2023. The research method used is descriptive. The data obtained in this study are presented directly without any analysis process. The sampling technique used was quota sampling of 50 respondents. The sample used is a urin sample during midstream. This research was conducted at the Redy Clinical Laboratory using the strip test method with the Egens Drug Test with 6 parameters, a positive results are marked with a red line in the control zone. The results of the study on 50 urin samples of workers in the city of Surakarta showed negative results for examination of Amphetamine, Methamphetamine, Cocaine, Morphine, THC and Benzodiazepines. Respondents in this study consisted of workers who worked in the sub-districts of Banjarsari (26%), Jebres (26%), Laweyan (14%), Pasar Kliwon (6%), Serengan (14%). The conclusion of this study was that 100% did not show the presence of amphetamine, methamphetamine, cocaine, morphine, THC, and benzodiazepines in the urin samples of workers in Surakarta.